Development and implementation of a fuzzy-neural network controller for brushless DC drives - Goekbulut, Mijanmer; Dandil, Beir; Bal, Cafer (Taylor & Francis Ltd, 2007)
In this paper, a Proportional-Derivative and Integral (PD-I) type Fuzzy-Neural Network Controller (FNNC) based on Sugeno fuzzy model is proposed for brushless DC drives to achieve satisfied performance under steady state and transient conditions. The proposed FNNC uses the speed error, change of error and the error integral as inputs. While the PD-FNNC is activated in transient states, the PI-FNNC is activated in steady state region. A transition mechanism between the PI and PD type fuzzy-neural controllers modifies the control law adaptively. The gradient descent algorithm is used to train the FNN in direct adaptive control scheme. Presented experimental results show the effectiveness of the proposed control system, by comparing the performance of various control approaches including PD type FNNC, PI type FNNC and conventional PI controller, under nonlinear loads and parameter variations of the motor.
Keywords: fuzzy-neural network; brushless DC drives; PD type FNNC; PI type FNNC; PD-I type FNNC